Implantation of in‐the‐bag capsular tension ring and toric intraocular lens for subluxated lens associated with large corneal astigmatism. Issue 2 (April 2017) - Chang, Pingjun; Li, Zhangliang; Lin, Lei; Wang, Shangrong; Xie, Jialu; Zhao, Yun‐e
Abstract : N/A: We present the case of a 56‐year‐old woman with Marfan syndrome and more than +4.0 diopters of corneal astigmatism. In the left eye, a capsular tension ring was used to extend the capsule and a capsule hook was used to prevent zonular dehiscence, capsular bag collapse, and vitreous prolapse. Phacoemulsification was performed using low parameters to keep the capsular bag stable during the surgery and protect the zonular fibers. During the 3‐year follow‐up, the toric intraocular lens remained stable in the capsular bag and the patient achieved excellent visual acuity and stable refractive results after surgery.